Track of courage [large type] - Warren, Susan May, 1966- (Call of the wild, 2026)
"Pop singer Keely Williams's search for her biological mother in Alaska has been painfully unsuccessful. Now she just wants to escape this wild frontier and never look back. But when her plane is hijacked, she's suddenly plunged into a race against not only an Alaska blizzard but also a killer who's on her tail. After a career-ending injury, ex-cop Dawson Mulligan has only one friend--Caspian, the stray dog he adopted. Dawson just wants to figure out how to get his life on track, but during a flight home to Copper Mountain, he spots a downed plane and stops to help. Except when his not-a-rescue dog runs off into the woods and discovers the trail of a missing survivor, it's up to the former cop to stage a rescue. But Dawson has no idea he's being pulled into a deadly pursuit, or that Caspian is more than he seems. There might be redemption and second chances waiting for both Dawson and Keely if they have the courage to face their wounded pasts and fight for their future."--